Semantic Enrichment of Web Data for the Provision of an Unified Data Repository of Brazilian Missing Persons - Gomes Jr., Jorão; Ferranti, Nicolas; de Souza, Jairo Francisco (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Communication and data technologies are becoming closely linked to people's lives. Therefore it is natural to make use of all this progress to reduce and solve social problems. In order for government and society to make the most appropriate decisions to deal with civilian disappearance, it's necessary to have a well-structured source of information. In several countries, it's difficult to access government data, since information is dispersed, not connected and poorly structured. So this work presents a framework to gather information on civil disappearance in Brazil through techniques such as Data Scraping and Linked Data. The goal is to make available an automatic data centralization of these individual cases, and to encourage the use of standards for the publication of data that are frequently ignored by organizations, hindering analysis and decision making on data.